Applied Numerical Methods for Scientists and Engineers - Edeo, Abdurkadir (LAP LAMBERT Academic Publishing, 2020)
This book presents a systematic and comprehensive explanation to numerical methods relevant in the different fields of engineering and applied sciences. Mathematical concepts and various techniques are presented in a clear, logical, and concise manner. Various visual features are used to highlight focus areas. Complete illustrative diagrams and MATLAB programs are used to facilitate mathematical modeling and solutions of application problems. Readers are motivated by a focus on the relevance of numerical methods through their applications in various engineering and applied science disciplines. Studies of various types of numerical methods are determined by engineering and science applications. This book is suitable for use not only as a textbook but also as a guide to self-study. It can also be used as a reference after students have completed learning the subject.